Substitusi Tepung Kacang Koro Terhadap Sifat Organoleptik Dan Kadar Air Tempani - Baiq Winda Syamsuriana; Iketut Swirya Jaya; Reni Sofiyatin; AASP Chandradewi (Poltekkes Kemenkes Mataram, 2017)
Background. Tempani is one of the traditional pastry products are often used in ceremonies in communities in a number of regions in Indonesia . Lentils flour is flour obtained by grinding seeds of lentils . Protein -rich flour lentils contain good nutrition . ( Rini , A.W 2008) This product contains high protein amounted to 58.4 ± 4.5 % . Flour bioavailability Rich Protein lentils will increase with the decrease of the activity of anti - tripsinnya be 20.4 150.0 ± 1.6 units / g . Amylose levels are relatively high at 30.0 ± 2.0 % and Resistant Starch content of 7.97 g / 100 g contribute to the low value of the Glycemic Index Wheat Protein Rich lentils . Based on the nutritional characteristics , Wheat Protein -rich lentils well used.Research Methods. This study used an experimental method in the laboratory of experimental design in the form of completely randomized design (CRD) of the factors is the addition of flour lentils (t) consisting of five cedar treatments, t1 (50%), t2 (60%), t3 (70%), t4 (80%) and t5 (90%) respectively replicated 3 times so obtained 15 experimental units.Research Result. All of bean flour substitution did not significantly affect the color and moisture content of tempani and significant effect on the smell, flavor and texture of tempani. Colors get scores of panelists from 3.4 to 3.68, a score value odors from 2.56 to 3.4, a score value of flavor from 3.08 to 3.52, and texture scores from 2.48 to 3.20. The water content with an average value of 4.67% - 5.67%.Conclusion. All treatments are preferred in terms of color, t1 treatment (50%) and t2 (60%) are most preferred in terms of smell and taste and t1 treatment (50%) are most preferred in terms of the texture of Tempani. The test results of water content tempani that meets ISO standards are in treatment t4 (80%), ie 4.67% (SNI maximum of 5%). T2 treatment (60%) is a product that is recommended because it has the organoleptic properties are preferred.